HER2-positive gastric cancer and antibody treatment: state of the art and future developments - Scheck, Magdalena K.; Hofheinz, Ralf-Dieter; Lorenzen, Sylvie (Cancers, 2024)
Despite a decreasing incidence in Western countries, gastric cancer is among the most common cancer subtypes globally and is associated with one of the highest tumor-related mortality rates. Biomarkers play an increasing role in the treatment against gastric cancer. HER2 was one of the first biomarkers that found its way into clinical practice. Since the ToGA trial, trastuzumab has been part of first-line palliative chemotherapy in metastatic or unresectable gastric cancer. HER2-targeting agents, such as the tyrosine kinase inhibitor lapatinib, the antibody drug conjugate (ADC) trastuzumab-emtansine or dual HER2 inhibition (pertuzumab and trastuzumab), have been investigated in the second-line setting but led to negative study results. More recently, the ADC trastuzumab-deruxtecan was authorized after the failure of trastuzumab-based treatment. However, further improvements in HER2-directed therapy are required as resistance mechanisms and HER2 heterogeneity limit the existing treatment options. This review aims to give an overview of the current standard-of-care HER2-directed therapy in gastric cancer, as well as its challenges and future developments.